2020
DOI: 10.1101/mcs.a004879
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent de novo HSPD1 variant is associated with hypomyelinating leukodystrophy

Abstract: Standardization of the use of next-generation sequencing for the diagnosis of rare neurological disorders has made it possible to detect potential disease-causing genetic variations, including de novo variants. However, the lack of a clear pathogenic relevance of gene variants poses a critical limitation for translating this genetic information into clinical practice, increasing the necessity to perform functional assays. Genetic screening is currently recommended in the guidelines for diagnosis of hypomyelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…To evaluate whether disease-associated variations found in patients trigger similar changes in the mitochondrial proteome, we performed proteomics analysis of dermal fibroblasts from two patients carrying disease-associated HSPD1 variants and presenting with hypomyelination phenotype. Patient 1 (P1) is heterozygous for the de novo variation p.Leu47Val with the milder disease phenotype 14 and Patient 2 (P2) is homozygous for the p.Asp29Gly variant causing the severe lethal hypomyelinating leukodystrophy MitCHAP60 disease 12 . Functional assays have shown that both HSP60 variants possess residual chaperone activity 14,15 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate whether disease-associated variations found in patients trigger similar changes in the mitochondrial proteome, we performed proteomics analysis of dermal fibroblasts from two patients carrying disease-associated HSPD1 variants and presenting with hypomyelination phenotype. Patient 1 (P1) is heterozygous for the de novo variation p.Leu47Val with the milder disease phenotype 14 and Patient 2 (P2) is homozygous for the p.Asp29Gly variant causing the severe lethal hypomyelinating leukodystrophy MitCHAP60 disease 12 . Functional assays have shown that both HSP60 variants possess residual chaperone activity 14,15 .…”
Section: Resultsmentioning
confidence: 99%
“…Patient 1 (P1) is heterozygous for the de novo variation p.Leu47Val with the milder disease phenotype 14 and Patient 2 (P2) is homozygous for the p.Asp29Gly variant causing the severe lethal hypomyelinating leukodystrophy MitCHAP60 disease 12 . Functional assays have shown that both HSP60 variants possess residual chaperone activity 14,15 . In contrast to our D423A-HSP60 cell system, the proteomes of both patient cell lines, each compared to three healthy control individuals, showed mainly upregulation of differentially expressed proteins (Figures 3A and 3B) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, this procedure is combined with crucial limitations in diagnosis. WES has successfully displayed differential diagnostic efficiency, particularly in rare disease-causing variants, and has a significant potential in identification of de novo mutations [18][19][20].…”
Section: Discussionmentioning
confidence: 99%